AGENCY AT WORK: A METAPHOR ANALYSIS OF LESSON PLANNING AMONG ENGLISH LANGUAGE TEACHERS IN THE PHILIPPINES - Paolo Nino Valdez; Minie Rose Lapinid; Von Christopher Chua (TEFLIN Journal, 2024)
Lesson planning is a core skill teachers need to develop in implementing lessons effectively in the classroom. While metaphor research has been used in a range of contexts including in teacher education, metaphors associated with lesson planning among teachers in developing regions in the world remain underrepresented. Due to the importance of lesson planning in the implementation of the curriculum, investigating metaphors of lesson planning provides helpful insights on the beliefs of teachers in classroom practice resulting in effective instruction. This investigation sought to identify the metaphors Filipino teachers associate with lesson planning and their connections to teacher agency. This study, which is part of a larger investigation, examined metaphors from 73 English Language teacher-respondents in professional development workshops. The metaphorical conceptualization process employed in analyzing the data consists of three phases (1) validating and coding data, (2) summarizing and representing codes, and (3) identifying and describing categories. Results reveal eleven distinct conceptual categories, including perceptions of lesson planning as a project-like endeavor, an act of molding, and a form of creative expression, all of which highlight teacher agency in the teaching-learning process. These suggest that teachers take different roles in lesson planning depending on the nature of the subject matter, conditions they face in their work contexts, and their beliefs about teaching and learning. However, some teachers perceive lesson planning as routine and question its purpose, which poses challenges in designing effective professional development programs tailored to their needs.